Generation of suppressive blood cells for control of allograft rejection - Kleist, Christian; Şandra-Petrescu, Flavius Ionuţ; Jiga, Lucian; Dittmar, Laura; Mohr, Elisabeth; Greil, Johann; Mier, Walter; Becker, Luis Eduardo; Lang, Peter; Opelz, Gerhard; Terness, Peter (Clinical science, 2015)
Immunosuppressants, used to prevent organ rejection, cause serious side effects. We induced specific immunosuppression towards the foreign transplant by administration of mitomycin C (MMC)-treated blood cells (MICs) from the organ donor, thus circumventing additional immunosuppressive medication.
Published as immediate publication 11 December 2014
Gesehen am 07.07.2020